Proceedings of the 2002 International Symposium on Low Power Electronics and Design - ISLPED '02 2002
DOI: 10.1145/566439.566440
|View full text |Cite
|
Sign up to set email alerts
|

Low-power color TFT LCD display for hand-held embedded systems

Abstract: An LCD (Liquid Crystal Display) is a standard display device for hand-held embedded systems. Today, color TFT (Thin-Film Transistor) LCDs are common even in cost-effective equipments. An LCD display system is composed of an LCD panel, a frame buffer memory, an LCD and frame buffer controller, and a backlight inverter and lamp. All of them are heavy power consumers, and their portion becomes much more dominant when running interactive applications. This is because interactive applications are often triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…In [7], the authors introduced a backlight luminance dimming technique with brightness compensation or contrast enhancement. They modeled the intensity perceived by human eyes as a linear function of LCD transmittance, backlight luminance, and image luminance.…”
Section: Backlight Dimming With Brightness Compensation and Contrast mentioning
confidence: 99%
See 4 more Smart Citations
“…In [7], the authors introduced a backlight luminance dimming technique with brightness compensation or contrast enhancement. They modeled the intensity perceived by human eyes as a linear function of LCD transmittance, backlight luminance, and image luminance.…”
Section: Backlight Dimming With Brightness Compensation and Contrast mentioning
confidence: 99%
“…In the mean time, contrast enhancement is used for images with distinct color spectrums and it leads to more readable display and more aggressive power saving. [12] • Adaptive global backlight dimming [13] Low-power techniques with DVS • Variable duty-ratio refresh [7] • Variable dot clock and variable frame refresh [8] • Advanced DVS method [2] Software-based low-power techniques • Dynamic color depth control [7] • Liquid crystal orientation shift [8] Hardware-based low-power techniques • The use of LED instead of CCFL [14] • The use of advanced light guide [14] • The use of field sequential color system [14] • Chromatic encoding for digital visual interface (DVI) [15] From the experiments, the authors reported that the power saving reaches up to 200 mW, or around 6% of the total system power, while reducing the backlight luminance from 45 to 32 cd/m 2 . For contrast enhancement, the transformation of RGB values is found to be new_RGB min original_RGB* old_backlight_luminance new_bac 1,…”
Section: Backlight Dimming With Brightness Compensation and Contrast mentioning
confidence: 99%
See 3 more Smart Citations